INNOVATIVE PEDAGOGICAL TECHNOLOGIES FOR CORRECTING SPEECH DEFECTS BASED ON DEVELOPMENTAL GAMES IN SPEECH THERAPY CLASSES - Mamasiddiqova Muqaddam Sodiqjon qizi (Journals Park Publishing, 2025)
In this article innovative pedagogical technologies for correcting speech defects based on developmental games in speech therapy classes are analyzed on a scientific basis. Motivational, psychological and linguistic mechanisms of developmental games, their role in modern speech therapy practice, as well as their interaction with digital and multimodal interactive tools are studied. The proposed technologies serve to increase the effectiveness of the process of eliminating speech defects, to attract children's activity to speech therapy classes and to develop communicative competencies.
Keywords: Speech therapy, speech defects, educational gameplay, innovative technology, multimodal approach, interactive techniques.